Analisis Beban Kerja Pada Divisi SHU & IT PT Aneka Jasa Grhadika - Sholekhah Nur Aini; Maulidyah Amalina Rizqi (Jurnal Mahasiswa Manajemen, 2022)
Background – There are several employees on the SHU&IT Division PT Aneka Jasa Grhadika are experiencing the workload. In this research researchers want to know the cause of the workload and impact of workloads for employee work productivity. Objective - This study aims to determine the causes of the workload experienced by employees and determine the impact of workload on employee productivity. Design/methodology/approach - The study uses a qualitative approach with qualitative descriptive methods. The informant in this research is an employee who has experienced the workload and colleagues who are in the SHU&IT Division PT Aneka Jasa Grhadika with interview techniques by telephone and supported by the data documentation. Findings - The result of this research is that there are some employees who experienced the workload that caused the employee concurrently and the impact of workload on employee productivity is to be less maximal because of the job overload. Research Implications – From the results of this study there are several implications, namely to determine the workload on the object of research. As well as useful for analyzing workloads that are useful for job analysis on the object of research. Research Limitations - The limitation in this study is that it cannot find information from the General Manager of the SHU & IT Division so that information about measuring employee work productivity is only limited because the one holding the data is the General Manager of the SHU & IT Division of PT Aneka Jasa Grhadika.